MINKE’S DECOLONIZATION IN PRAMOEDYA ANANTA TOER’S CHILD OF ALL NATIONS - SAPRIYADI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
Abstrak Anak semua bangsa adalah salah satu novel dimana kekuatan colonial bekembang di hindi belanda. Disini penindasan belanda kepada petani gula menjadi topik utama. karakter Minke terlihat sangat vital karena Minke menjadi sosok yang menentukan alur cerita. Skripsi ini bertujuan meneliti tentang respon primbumi yang berintelektual seperti Minke untuk menghadapi kenyataan yang dibuat oleh Belanda. Di dalam novel Anak semua bangsa, Minke menjadi karakter utama yang mana mempunyai hubungan yang sangat membingungkan dengan pemerintahan Belanda. Skripsi ini ingin menunjukkan sisi lain dalam novel Anak semua bangsa yang mana membuahkan sebuah aksi dekolonialisasi. Disamping itu, skripsi ini juga ingin menunjukkan sebuah proses dimana seorang Minke mencapai sebuah aksi dekolonialisasi. Untuk memperoleh hasil dari tujuan yang diinginkan, skripsi ini mengumpulkan data utama dari novel itu sendiri dan juga dari internet. Untuk teori yang digunakan skripsi ini menggunakan teori dekolonisasi dari Frantz Fanon, Fanon menjelaskan tentang tiga fase yakni; asimilasi, penemuan jati diri, dan perjuangan, dan hasilnya memberikan hasil dimana terlahirlah jiwa kemanusiaan Minke, dan sjkripsi ini juga menunjukkan perjuangan seorang Minke yang mana tergambar dari cerita dan percakapan yang dilakukan Minke. Kata Kunci: kolonisasi, dekolonisasi, jiwa kemanusiaan, asimilasi, penemuan jati diri, perjuangan Abstract Child of All Nations is the one of novel that gives a picture how the power colonization exist in the Dutch East Indies. Dutch oppression is underlined by a look at the exploitation of East Java’s peasants by sugar plantation owners, local ruler and Dutch officials. Minke character is really important because he decides how the story goes. This study aims to observe more about the respond native intellectual such as Minke to face the reality that created by Dutch. In the Child of All Nations, Minke becomes the main character which has complicated relationship with Dutch. This study wants to show how the story of Child of All Nations creates decolonization. There are actually many factors, in which forces Minke to create decolonization. Besides that, this study also wants to show the process of Minke reached that decolonization. To obtain the results of those purposes, this study uses three methods: data, theoretical approach, and procedure of analysis. This study collects primary data from the Child of All Nations novel and the internet. For theoretical approach, this study uses theory of decolonization, in which brought by Frantz Fanon. Fanon explain decolonization in the three phases, there are; assimilation, self discovery, fighting back. After using those theories, the results will be the process of creating humanity side in the life of Minke. From that result, this study is able to show the process of becoming the real of revolutionary in Minke’s life, using conversations and narrations in the story. There will be some changes in Minke which are represented by story and his conversation as the process of becoming a revolutionary. Keywords: colonization, decolonization, humanity, assimilation, self discovery, revolutionary.